If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 24 = -6x Reorder the terms: 24 + 2x = -6x Solving 24 + 2x = -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 24 + 2x + 6x = -6x + 6x Combine like terms: 2x + 6x = 8x 24 + 8x = -6x + 6x Combine like terms: -6x + 6x = 0 24 + 8x = 0 Add '-24' to each side of the equation. 24 + -24 + 8x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 8x = 0 + -24 8x = 0 + -24 Combine like terms: 0 + -24 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| 3x-40+x-y=180 | | x-.3x=160 | | 2x-(-2z)+3z=-1 | | b-1*16=1 | | -2(x+2)=2x+t | | 7p-(13p+4)=-2(2p-1)+10 | | x-.3x=300 | | (4y-3)(7y+6)= | | 7m+5=21 | | 2y^2-8y=7 | | y/4+5=3(y-2) | | 0.10a+.011(a+3000)=1380 | | 3(2n+5)-3n=2(n+5)-3(2n-4) | | 3y^2-51y+90= | | 2d-3+3c-2d-3+3c=4d-12+6c | | -x-16=-5x | | y=-2.7x^2+30x+6.5 | | 93.96=4.7p+8.79p-2.6p | | 3(x+2)=9x+1-6x+5 | | -4(-5x-4)=-44 | | x-.3x=200 | | 5.1-x=20.3 | | .25(-8x+8)=-2+2x | | x^2-13x*y+40y^2=0 | | 2(7d-6)+8= | | lx+2l=-lx-2l | | 50-10(4-2)+6= | | 0.56x-0.86=11.35-2.74x | | -5x+12=-3x-6 | | .25(-8x-8x)=-2+2x | | 4(x+6)=3x-2 | | 5x+12=-3x-6 |